Cellular Metabolism and Macrophage Functional Polarization. (2nd January 2015) - Zhu, Linnan; Zhao, Qingjie; Yang, Tao; Ding, Wenjun; Zhao, Yong
<x xml:space="preserve">Abstract</x> Macrophages are a functionally heterogeneous cell population that is mainly shaped by a variety of microenvironmental stimuli. Interferon γ (IFN-γ), interleukin-1β (IL-1β), and lipopolysaccharide (LPS) induce a classical activation of macrophages (M1), whereas IL-4 and IL-13 induce an alternative activation program in macrophages (M2). Reprogramming of intracellular metabolisms is required for the proper polarization and functions of activated macrophages. Similar to the Warburg effect observed in tumor cells, M1 macrophages increase glucose consumption and lactate release and decreased oxygen consumption rate. In comparison, M2 macrophages mainly employ oxidative glucose metabolism pathways. In addition, fatty acids, vitamins, and iron metabolisms are also related to macrophage polarization. However, detailed metabolic pathways involved in macrophages have remained elusive. Understanding the bidirectional interactions between cellular metabolism and macrophage functions in physiological and pathological situations and the regulatory pathways involved may offer novel therapies for macrophage-associated diseases.